Embedding and sparing of lamellar hole–associated epiretinal proliferation in the treatment of lamellar macular holes - Lai, Tso-Ting; Hsieh, Yi-Ting; Lee, Young; Yang, Chung-May (Eye (London), 2022)
Objectives Compare the outcomes of two surgical techniques, lamellar hole–associated epiretinal proliferation (LHEP) embedding and LHEP sparing, in treating idiopathic lamellar macular holes (LMHs). Methods Retrospective consecutive case series with 34 LMHs with LHEP that underwent operation. LHEP-sparing technique was used before July 2015 and LHEP-embedding after July 2015. Morphological features in optical coherence tomography (OCT) images were identified, including the presence of LHEP, ellipsoid zone (EZ) defects, and types of LMH closure, along with best-corrected visual acuity (BCVA) before and after surgery. Results No baseline differences were observed between the embedding (17 patients) and sparing (17 patients) groups in LMH size, retinal defect depth, or preoperative BCVA. The two groups’ mean postoperative BCVAs were similar (embedding vs sparing: 0.388 ± 0.337 vs 0.465 ± 0.418 [Snellen: 20/49 and 20/58], P = 0.812). Postoperatively, a U-type closure was observed in 77 and 65% of patients in the embedding and sparing groups, respectively. Both groups exhibited V-type and T-type closures in half of the remaining patients ( P = 0.753). Older age, postoperative external limiting membrane defect, postoperative EZ disruption, and non–U-type closure were associated with worse final BCVA. Conclusions Both the LHEP-embedding and LHEP-sparing techniques significantly improved vision in patients with LMHs and produced similar visual and anatomical outcomes. Most patients achieved a normal U-type closure with either technique. Preservation of LHEP during surgery is vital and could facilitates successful surgery.